2021
DOI: 10.1177/11297298211044325
|View full text |Cite
|
Sign up to set email alerts
|

ECHOTIP: A structured protocol for ultrasound-based tip navigation and tip location during placement of central venous access devices in adult patients

Abstract: Central venous access devices are routinely used in clinical practice for administration of fluids and medications, for drawing blood samples and for hemodynamic monitoring. The adoption of ultrasound guided venipuncture has significantly reduced procedure-related complications, as documented by the recommendations of most recent guidelines. Ultrasound has also an important role also in other aspects of central venous catheterization, such as in the pre-procedural evaluation of the venous patrimony and in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…2 More recently, specific “insertion bundles” have been implemented to reduce any type of complication due to central venous catheterization in adults. 35 Most of these bundles include pivotal recommendations such as: (a) use of ultrasound for the choice of the vein, for real time ultrasound-guided venipuncture, for tip navigation, tip location, and for early detection of complications 6 ; (b) proper choice of the exit site 7,8 ; (c) skin antisepsis using 2% chlorhexidine in alcohol 9 ; (d) maximal barrier precautions 9 ; (e) intraprocedural tip location by intracavitary ECG 10 or ultrasound 11 ; (f) consistent use of sutureless devices 9 ; (g) use of cyanoacrylate glue for sealing the exit site. 12,13 All these new methodologies and technologies have contributed to reduce the incidence of complications, increasing the cost-effectiveness of CVAD insertion in adults.…”
Section: Introductionmentioning
confidence: 99%
“…2 More recently, specific “insertion bundles” have been implemented to reduce any type of complication due to central venous catheterization in adults. 35 Most of these bundles include pivotal recommendations such as: (a) use of ultrasound for the choice of the vein, for real time ultrasound-guided venipuncture, for tip navigation, tip location, and for early detection of complications 6 ; (b) proper choice of the exit site 7,8 ; (c) skin antisepsis using 2% chlorhexidine in alcohol 9 ; (d) maximal barrier precautions 9 ; (e) intraprocedural tip location by intracavitary ECG 10 or ultrasound 11 ; (f) consistent use of sutureless devices 9 ; (g) use of cyanoacrylate glue for sealing the exit site. 12,13 All these new methodologies and technologies have contributed to reduce the incidence of complications, increasing the cost-effectiveness of CVAD insertion in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that ultrasound and intracavitary electrocardiography can be used for tip location and navigation. 12,13 The sensitivity and success rate were higher in the group using these devices than in that using anatomical landmarks to confirm the catheter tip location. 13 Although these methods completely avoid the need for fluoroscopy and/or chest radiography, these methods can be safe and useful options for assessing PICC at non-applicable status to fluoroscopy or emergency.…”
Section: Discussionmentioning
confidence: 92%
“…37 Studies have also shown that the use of agitated saline with trans thoracic echocardiography (TTE) or transesophageal echocardiography (TEE) and more recently, the ECHOTIP protocol developed by La Greca and colleagues, to be effective in confirming catheter position in the SVC/RA. [38][39][40][41] However, these techniques require more advanced ultrasound skills and more than one operator to undertake appropriate ultrasound scanning, and may not be feasible for many institutions. A combination of both intra procedural scanning and IC ECG would be ideal if resources permitted.…”
Section: Discussionmentioning
confidence: 99%